AN AGE-DEPENDENT EXPANSION OF GAMMA DELTA T CELLS IN VISCERAL ADIPOSE TISSUE PROMOTES INFLAMMATION. (11th November 2018) - Powell, W; Steele, A; Balasuriya, B; Mori, S; Cohen, D; Starr, M
Abstract: Chronic inflammation originating from adipose tissue, even in the absence of obesity, is strongly linked to the development of cardiometabolic disorders. To date, the majority of research in this area has focused on obesity without regard for aging, despite the fact that aging often poses a larger risk. The objective of this study was to identify age-specific alterations in adipose tissue physiology which may underlie chronic inflammation. Our previous microarray analyses of visceral adipose tissue from young (4-mo) and aged (24-mo) mice showed evidence of increased T cell populations in the aged, including a 6-fold increase in gene expression of T cell receptor gamma (PMC3633415). In the present study using flow cytometry, we found that visceral adipose tissues of aged mice contain 5-fold more gamma delta (γδ)-T cells than that of young mice (p<0.01). This expansion was unique to visceral fat, not being observed in subcutaneous fat, spleen, blood, or skin. We further identified that adipose tissue γδ-T cells are CD44hiCD62low and are positive for CD69, suggesting a tissue-resident memory T cell phenotype (TRM). Using T cell receptor delta (TCRδ) knockout mice, we found that genetic deficiency of γδ-T cells significantly diminished the inflammatory response (measured by IL-6 production) of aged adipose tissues to ex vivo stimulation (p<0.01). Additionally, adipose tissues from aged TCRδ-/- mice exhibited reduced expression of senescent cell marker p16Ink4a compared to age-matched wild-type mice. Collectively, these findings suggest that expansion of a TRM γδ-T cell population in visceral adipose tissues contributes to age-related chronic inflammation.